Daytime QT by Routine 12-Lead ECG Is Prolonged in Patients with Severe Obstructive Sleep Apnea. (5th February 2020) - Walker, McCall; Blackwell, Jacob N.; Stafford, Patrick; Patel, Paras; Mazimba, Sula; Mehta, Nishaki; Cho, Yeilim; Mangrum, Michael; Nazarian, Saman; Bilchick, Kenneth; Kwon, Younghoon
Abstract : Background . Obstructive sleep apnea (OSA) has been linked to sudden cardiac death (SCD). Prolonged QT is a recognized electrocardiographic (ECG) marker of abnormal ventricular repolarization linked to increased risk of SCD. We hypothesized that individuals with OSA have more pronounced abnormality in daytime QT interval. Methods . We reviewed consecutive patients who underwent clinically indicated polysomnography with 12-lead ECG within 1 year at a single center. Heart rate-corrected QT interval (QTc) was compared by OSA severity class (normal/mild: apnea ‐ hypopnea index AHI < 15 / hr (n = 72 ); moderate: 15-30 (n = 72 ); severe: >30 (n = 105 )) adjusting for body mass index, age, sex, hypertension, and heart failure. Further evaluation was performed by dividing patients into severe (AHI > 30 ) and nonsevere (<30) OSA. Logistic analysis was used to determine association of OSA severity and abnormal QTc (>450/>470 ms for men/women, respectively). Results . A total of 249 patients were included. QTc was similar between the normal/mild and moderate groups, and the overall QTc trend increased across OSA (normal/mild: 435.6 ms; moderate: 431.36; severe: 444.4; p trend = 0.03 ). Abnormal QTc was found amongst 34% of male and 31% of female patients. Patients with severe OSA had longer QTc compared with normal/mild OSA (mean difference (95% CI): 10.0 ms (0.5, 19.0), p = 0.04 ). When stratified dichotomously (as opposed to three groups), patients with severe OSA again had longer QTc (vs. nonsevere OSA) (444.4 ms vs. 433.48 ms, p = 0.004 ). Severe OSA was also associated with abnormal QTc (OR (95% CI): 2.68 (1.34, 5.48), p = 0.006 ). Conclusions . In a sleep clinic cohort, severe OSA was associated with higher QTc and clinically defined abnormal QTc compared with nonsevere OSA.